Thickness Calculation of Thin Transparent Conductive Membrane on the Border with a Magnetic Fluid - V.V. Chekanov; N.V. Kandaurova; V.S. Chekanov (Журнал нано- та електронної фізики)
The determination method of the membrane thickness of ITO (InSnO2). The magnetite nanoparticles in the electric field migrate, forming the thin layer near conductive ITO membrane with varying thickness. Lighting this structure by monochromatic plane polarized light the interference of light in the thin membrane was observed. The experimental values of the intensity of the reflected light from the surface of «ITO – layer of magnetite particles" for samples with different thickness of the conductive coating.